Pengembangan Media Pembelajaran Berbasis Augmented Reality pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMAN 1 Bukittinggi - Afifah Alya Khulqi; Wedra Aprison (YASIN, 2026)
Although the use of digital technology in learning has been widely studied, the development of Augmented Reality-based learning media in Islamic Religious Education and Character Education at the senior high school level remains relatively limited. This study aimed to develop Augmented Reality-based learning media and assess its feasibility as an innovative learning tool in Islamic Religious Education and Character Education at SMAN 1 Bukittinggi. This study employed a Research and Development approach using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The study involved media experts, material experts, language experts, and students as users of the developed media. Data were collected through interviews, observations, documentation, and Likert-scale validation questionnaires, and then analyzed using descriptive quantitative and qualitative methods to determine the feasibility level of the media. The results showed that the developed Augmented Reality-based learning media had a very high level of feasibility, with media expert validation results of 87.5%, material expert validation of 88.8%, and language expert validation of 93.75%, with an overall average of 90%, which falls into the very valid category. These findings confirm that the media is feasible for use as an innovative learning medium to support the quality of the learning process in Islamic Religious Education and Character Education. Thus, this study contributes to strengthening the literature on the use of Augmented Reality in religious learning while also providing practical implications for teachers and educational institutions in developing interactive learning media based on digital technology, as well as opening opportunities for further studies on its effectiveness in relation to student learning outcomes and motivation.